Earthquake loss estimation for the Kathmandu Valley - Chaulagain, Hemchandra (2014)
The capital city, Kathmandu, is the most developed and populated place in Nepal. The majority of the administrative offices, headquarters, numerous historical monuments, and eight World Heritages sites are in the Kathmandu Valley. However, this region is geologically located on lacustrine sediment basin, characterized by a long history of destructive earthquakes. The past events resulted in great damage of structures, losses of human life’s and property, and interrupted the social development. Therefore, earthquake disaster management is one of the most serious issues in highly seismically active regions such as the Kathmandu Valley. In recent years, the earthquake risk in this area has significantly increased due to uncontrolled development, poor construction practices with no earthquake safety consideration, and lack of awareness amongst the general public and government authorities. In this context, this study explores the realistic situation of earthquake losses due to future earthquakes in Kathmandu Valley. To this end, three municipalities: (a) Kathmandu metropolitan city (KMC), (b) Lalitpur Sub-Metropolitan City (LSMC) and (c) Bhaktapur Municipality (BMC) are selected for study. The earthquake loss estimation in the selected municipalities is performed through the combination of seismic hazard, structural vulnerability, and exposure data. For what concerns the seismic input, various earthquake scenarios considering four seismic sources in Nepal were adopted. Regarding the exposure, data about the type of existing buildings, population, and ward level distribution of building typologies is estimated from the recent national census survey of 2011. The economic losses due to the scenario earthquakes are determined using fragility functions. The commonly used standard fragility curves are adopted for adobe, brick/stone with mud mortar buildings, and brick/stone with cement mortar buildings. For the reinforced concrete structures, a new fragility model was derived considering four construction typologies: i) current construction practices (CCP), ii) structures according to the Nepal buildings code (NBC), iii) structures according to the modified Nepal building code (NBC+) and iv) well designed structures (WDS). In this study, a set of fragility functions is converted into a vulnerability model through a consequences model. Finally, the ward level distribution of damage for each building typology, building losses and the corresponding economic loss for each scenario earthquake is obtained using the OpenQuake-engine. The distribution of damage within the Kathmandu Valley is currently being employing in the development of a shelter model for the region, involving various local authorities and decision makers.